Enhancing Shelf Life of Vegetable Oils Blend by Using Moringa oleifera Leaf Extract as Antioxidant: Antioxidant Activity of Moringa oleifera on Vegetable Oil (Biological Sciences - PJSIR, 2015)
The antioxidant activity of ethanolic Moringa oleifera leaf extract for oxidative stabilisation of canola, sunflower and soybean oils was investigated at ambient temperature. The blend was prepared by mixing canola, sunflower and soybean oils in equal proportions. Ethanolic M. oleifera leaf extract was incorporated into vegetable oils blend at three different concentrations; 300, 600 and 900 ppm (T1, T2 and T3), compared with a control and the sample added with 100 ppm tertiary butylated hydroxyl quinine (TBHQ) was used as a positive control. Filled in one litre transparent PET bottles, kept at room tempera- ture (35-40 °C) for 3 months and sampled at 0 and 90 days for the assessment of oxidative stability. Peroxide value of three months stored blank, T3 and TBHQ supplemented samples were 2.25, 0.84 and 0.78 (meqO2/kg). Induction period of blank, T3 and TBHQ supplemented vegetable oils blend was 3.46, 7.95 and 8.57 h. Peroxide value of blank, T3 and TBHQ supplemented vegetable oils blend, after 5 days at 63 °C, was 7.55, 2.81 and 2.59 (meqO2/kg).